The Knowledge: how to get the information you need out of your computers and information systems. - Mike Gatehouse; June Statham; Harriet Ward (2004)
Information systems in current use in children’s social services, whether computer- or paper-based, are generally designed more for recording information than for retrieving and using it, especially in daily practice. This severely limits their usefulness and reduces the quality of the data they contain—users of a system who get nothing out of it are unlikely to care much about what they put in. This practical guide for local authority social services departments aims to show how that situation can be remedied—how you can exploit the information capital you accumulate in your daily operations to empower your staff and improve the quality of outcomes for the children and families you serve. The key is outputs: what you retrieve from your information systems. Most information systems are quite capable of producing outputs, but do so poorly, if at all, because time and resources have not been assigned to identifying and specifying the outputs that are required, who needs them and how they will be used. With most local authorities at present planning changes to their systems in order to implement the Integrated Children’s System, now is the time to include outputs in the specifications. The cost of providing outputs will be much lower if they are incorporated at this stage than if they are requested as piecemeal additions to an established system. While it may not be possible to obtain immediately all the outputs we describe in this report, the addition of even some of them should considerably improve the quality and usefulness of your information system. This guide is based on research commissioned by the DH/DfES, which involved consultation with childcare and IT experts in 13 local authorities in England and Wales, followed by detailed discussions with over fifty staff working at all levels in six authorities. It provides a methodology for describing and categorising outputs, identifies some of those required at each level of a children’s services department and provides clear advice to staff at each level on the steps they can take to obtain the outputs they require.